Periapical Bone Lesions and Radiographic Features - NAMDAR PEKİNER, FİLİZ MEDİHA; KESER, GAYE (MARMARA UNIV, INST HEALTH SCIENCES, 2017)
Periapical bone lesions are frequently seen in dentistry and may lead to tooth loss when not treated. Dental radiographic imaging is an important tool for making an accurate diagnosis and for performing clinical examinations in endodontic treatment. Panoramic and periapical radiographic techniques provide adequate information, yet these techniques provide a two-dimensional representation of three-dimensional structures. Recently, cone-beam computed tomography (CBCT) systems have become available for the three-dimensional visualization of the craniofacial complex and periapical bone lesions, and the evaluation of periapical bone lesions with CBCT improves the prognosis of the current treatment pathology and prevents possible bone destruction. This article presents periapical bone lesions and radiographic features.
Keywords: Periapical lesion; radiology; panoramic radiography; cone beam computed tomography; BEAM COMPUTED-TOMOGRAPHY; ROOT-FILLED TEETH; ENDODONTICALLY TREATED TEETH; APICAL PERIODONTITIS; CORONAL RESTORATIONS; QUALITY; POPULATION; HEALTH; PREVALENCE; ADULT